Implementasi Program Tahfidzul Qur’an Dalam Membentuk Karakter Religius Di MA Al-Islam Jamsaren Surakarta - Kukuh Nugroho; Sukari (4, 2024)
This study aims to determine how the implementation of the Qur'an memorization program in shaping the religious character of students at MA Al-Islam Jamsaren Surakarta. This study uses a qualitative descriptive method with research subjects consisting of the principal and teachers at MA Al-Islam Jamsaren Surakarta. This Madrasah is an educational institution with Islamic characteristics based on the Qur'an and As-Sunnah, so the Qur'an memorization program is an important part in supporting the educational vision and mission. Research data were obtained through observation, interviews, documentation, and supported by relevant literature. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions to produce a comprehensive picture of the program implementation. The results of the study indicate that MA Al-Islam Jamsaren Surakarta has implemented the Qur'an memorization program well, although in practice there are still some limitations. This program has been proven to have a positive impact in shaping the religious character of students. Religious values ​​that have been successfully instilled include honesty, which is reflected in the students' attitudes in maintaining the mandate of memorization; politeness in behaving towards teachers and others; independence in managing study time and murojaah; and responsibility for academic and non-academic tasks. Furthermore, a caring attitude for others also develops through social interactions based on Qur'anic values. Thus, the Qur'an memorization program not only serves as a means of improving the quality of Qur'an memorization but also serves as a strategic instrument in shaping students' noble character. This aligns with the primary goal of Islamic education, namely to produce a generation of Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana implementasi program tahfidzul Qur’an dalam membentuk karakter religius peserta didik di MA Al-Islam Jamsaren Surakarta. Penelitian ini menggunakan metode deskriptif kualitatif dengan subjek penelitian terdiri dari kepala madrasah dan guru-guru di MA Al-Islam Jamsaren Surakarta. Madrasah ini merupakan lembaga pendidikan berciri khas Islam yang berlandaskan Al-Qur’an dan As-Sunnah, sehingga program tahfidzul Qur’an menjadi bagian penting dalam mendukung visi dan misi pendidikan. Data penelitian diperoleh melalui observasi, wawancara, dokumentasi, serta ditunjang dengan literatur yang relevan. Analisis data dilakukan melalui tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan sehingga menghasilkan gambaran komprehensif mengenai pelaksanaan program. Hasil penelitian menunjukkan bahwa MA Al-Islam Jamsaren Surakarta telah menerapkan program tahfidzul Qur’an dengan baik, meskipun dalam praktiknya masih terdapat beberapa keterbatasan. Program ini terbukti mampu memberikan dampak positif dalam membentuk karakter religius peserta didik. Nilai-nilai religius yang berhasil ditanamkan di antaranya adalah kejujuran, yang tercermin dari sikap siswa dalam menjaga amanah hafalan; sopan santun dalam bersikap kepada guru maupun sesama; kemandirian dalam mengatur waktu belajar dan murojaah; serta tanggung jawab terhadap tugas-tugas akademik maupun non-akademik. Selain itu, sikap peduli kepada sesama juga tumbuh melalui interaksi sosial yang dilandasi nilai-nilai Qur’ani. Dengan demikian, program tahfidzul Qur’an tidak hanya berfungsi sebagai sarana meningkatkan kualitas hafalan Al-Qur’an, tetapi juga menjadi instrumen strategis dalam membentuk akhlak mulia peserta didik. Hal ini sejalan dengan tujuan utama pendidikan Islam, yakni mencetak generasi